2016
DOI: 10.1002/jaba.340
|View full text |Cite
|
Sign up to set email alerts
|

The use of matrix training to promote generative language with children with autism

Abstract: Matrix training consists of planning instruction by arranging components of desired skills across 2 axes. After training with diagonal targets that each combine 2 unique skill components, responses to nondiagonal targets, consisting of novel combinations of the components, may emerge. A multiple-probe design across participants was used to evaluate matrix training with known nouns (e.g., cat) and verbs (e.g., jumping) with 5 children with autism spectrum disorders (ASD). Following baseline of Matrix 1 and a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
69
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(88 citation statements)
references
References 26 publications
(46 reference statements)
17
69
1
1
Order By: Relevance
“…Constructing sentences is a language milestone that depends on learning (Mackay, 2013;Papalia & Olds, 2000). It requires abstracting syntactic rules, categorizing words in classes, and establishing relations between words (or classes of words) that occupy a specific position in a sentence (Frampton, Wymer, Hansen, & Shillingsburg, 2016;Mackay, 2013). Order (or lexical responding) is at the base of such learning (Goldstein, Angelo, & Mousetis, 1987;Mackay, 2013;Skinner, 1957).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructing sentences is a language milestone that depends on learning (Mackay, 2013;Papalia & Olds, 2000). It requires abstracting syntactic rules, categorizing words in classes, and establishing relations between words (or classes of words) that occupy a specific position in a sentence (Frampton, Wymer, Hansen, & Shillingsburg, 2016;Mackay, 2013). Order (or lexical responding) is at the base of such learning (Goldstein, Angelo, & Mousetis, 1987;Mackay, 2013;Skinner, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…Order (or lexical responding) is at the base of such learning (Goldstein, Angelo, & Mousetis, 1987;Mackay, 2013;Skinner, 1957). Sentence productivity derives from recombinative generalization, in which the learner produces novel combinations by recombining words that were previously trained and arranged in order (Frampton et al, 2016;Goldstein, 1983b;Goldstein & Mousetis, 1989;Yamamoto & Miya, 1999). Some procedures can promote order-word relations and sentence productivity, such as matrix training (Axe & Sainato, 2010;Frampton et al, 2016;Goldstein, 1983a), CRMTS (Mackay, 2013), and matrix and CRMTS combined (Yamamoto & Miya, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…To create meaningful, general, and lasting behavior change often requires a synthesis of assessment and intervention components of known efficacy. It has also become clearer over time that these synthesized or packaged interventions (e.g., Lovaas, ) can occasion the next generation of highly analytic research (e.g., Cariveau, Kodak, & Campbell, ; Fisher, Pawich, Dickes, Paden, & Toussaint, ; Frampton, Wymer, Hansen, & Shillingsburg, ; Grow, Carr, Kodak, Jostad, & Kisamore, ; Plaisance, Lerman, Laudont, & Wu, ; Vladescu & Kodak, ). Descriptions of synthesized interventions and evaluations of their effects are therefore welcome in JABA , partly so that meaningful and lasting behavior change may be showcased in this journal and partly so that new lines of highly analytic research may be occasioned.…”
Section: A Renewed Emphasis On Effectivenessmentioning
confidence: 99%
“…Matrix training has been shown to produce generative responding for a variety of tact combinations such as noun–verb (Frampton, Wymer, Hansen, & Shillingsburg, ), object–preposition (Pauwels, Ahearn, & Cohen, ), and subject–verb–object (Kohler & Malott, ). A recent matrix training review that focused on individuals with autism spectrum disorder found that there is the potential for learning to occur from direct teaching for approximately 31% of selected target combinations and the remaining 69% to occur through recombinative generalization (Curiel et al, ).…”
Section: Introductionmentioning
confidence: 99%